Aspectos epidemiológicos, clínicos e lesões vesicais na intoxicação crônica espontânea por Pteridium aquilinum em bovinos - Gabriel, Adriane Loy (2008)
Spontaneous cases of chronic poisoning by Pteridium aquilinum in cattle were studied. The clinical forms of the disease were squamous cell carcinoma (SCCs) of the upper digestive tract (UDT) and bovine enzootic hematuria (BEH). The cases were from the midland Region of the Midwest of Rio Grande do Sul State, Brazil. For the epidemiological study, the profile of the farms was analyzed about herd purpose, main activity of the farm, altitude, and area of plant infestation. No differences were observed among the clinical forms, according to these criteria. Analysis of the ager, gender, and breed of the affected cattle revealed that, in both clinical forms of disease, mixed breed cows (more common in that region) were more affected. In BEH, adult cattle (3-to-7-years-old) were more frequently affected. In the form of UDT SCCs, aged cattle (more than 8- years-old) were more affected. For the clinical study, clinical signs and blood work were evaluated at terminal phase of disease. Cattle with UDT SCCs, had progressive weigth loss, ruminal atony, cough, dysphagia, bloating, and regurgitation. Hematuria was clinically observed in one case of this disease form. In cattle with BEH, hematuria was observed in all cases, followed by progresive weigth loss. Non-regenerative anemia was detected in 33.33% in UDT SCCs form and in 66.66% of BEH form. Changes in white blood count occurred in some cases but drop in lymphocytes was uncommon in both forms of disease. For the morfological study, urinary bladders of 46 UDT SCCs cases and 11 BEH cases were analyzed. Grossly, 16/46 bladders of the UDT SCCs form had gross lesions (vesical red or pale nodules, hemorrhages, and papilomas; red urine in the three cases). In BEH form, the bladder had nodules, large neoplastic masses, red urine, papilomas, and hemorrhages. Pielonephritis and hidronephosis were seen in a few cases. Microscopically, in the UDT SCCs form, 44/46 (95.65%) bladders had 22 different types of morphological changes, caracterized by neoplastic lesions (5/22) and non-neoplastic lesions (17/22), which were subdivided in non-neoplastic epithelial changes (6/17), general changes of the lamina propria (6/17), and inflammatory changes (5/17). The bladder changes in BEH form were of 19 different types, caracterized by neoplastic lesions (5/19) and non-neoplastic lesions (14/19), which were subdivided in non-neoplastic epitelial changes (9/14), general changes of the lamina propria (3/14), and inflammatory changes (2/14). In BEH, mesenchymal neoplasms were more observed than epithelial ones, and most of them were malignant. Immunohistochemistry was utilized to characterize the histogenesis of poorly differentiated neoplasms. In conclusion, the morfological study showed that urinary bladder lesions are very often in cattle with the UDT SCCs form, and were identical to the ones seen in cattle with BEH.